Online Bussiness Interest Factor Analysis for Students - Siregar, Melinda; Nasution, Siti Aisyah (Universitas Malikussaleh, 2020)
This study aims to see how the factors that arise on the interests that affect students in doing business online. Online business has several factors that influence the development of student interest. Some students think that they will become unemployed after college, or that they will find it difficult to get a job later, and so on. From the results of the research conducted, it was found that there were educational and environmental factors that were very influential in the progress of student interest in doing online business. The sample used in this study were 20 students from the entire student population. The method used in this research is survey method and quantitative analysis method. This study uses a questionnaire instrument in data collection. The data obtained in the education factor is the t-count value of the education variable> from the t-table, namely (3.251> 2.086) and a significant value (0.000 <0.05). And for environmental factors, the t-count value for environmental variables is <than the t-table value, namely (1.552 <2, 086) and a significant value (0.255> 0.05). From the test results, the value of the F table is 2.71 at the level of alpha = 0.05 degrees of freedom of the numerator 3 and the denominator is 16. Obtained F count is 4.513> than the F table is 3.10. This comparison shows that the influence of education and environmental factors simultaneously has an impact on student interest in doing business online.